Conditions when abelian clean Bezout ring is an elementary divisors ring (in Ukrainian) - I. S. Vasyunyk (Математичні Студії, 2012)
In the paper it is proved that the abelian clean Bezout ring is an elementary divisors ring, if and only if it is a duo-ring and shows that the projective-free right (left) Bezout ring is right (left) Hermite ring if his stable rank not more 2.